Pulmonary delivery of siRNA against acute lung injury/acute respiratory distress syndrome - Makhloufi Zoulikha; Qingqing Xiao; George Frimpong Boafo; Marwa A. Sallam; Zhongjian Chen; Wei He (Elsevier, 2022)
The use of small interfering RNAs (siRNAs) has been under investigation for the treatment of several unmet medical needs, including acute lung injury/acute respiratory distress syndrome (ALI/ARDS) wherein siRNA may be implemented to modify the expression of pro-inflammatory cytokines and chemokines at the mRNA level. The properties such as clear anatomy, accessibility, and relatively low enzyme activity make the lung a good target for local siRNA therapy. However, the translation of siRNA is restricted by the inefficient delivery of siRNA therapeutics to the target cells due to the properties of naked siRNA. Thus, this review will focus on the various delivery systems that can be used and the different barriers that need to be surmounted for the development of stable inhalable siRNA formulations for human use before siRNA therapeutics for ALI/ARDS become available in the clinic.